Root-mycorrhizae species and variety pairing matters: A study case with arbuscular mycorrhizal fungi communities and Vitis vinifera varieties in the southern Brazil - de Souza, Tancredo Augusto Feitosa; dos Santos Nascimento, Gislaine; da Silva, Lucas Jónatan Rodrigues [UNESP]; Welter, Leocir José (Elsevier, 2024)
Vitis vinifera varieties can change the arbuscular mycorrhizal fungi (AMF) community structure in their rhizosphere. Our aim here was to present a quantitative analysis of the AMF species associated with V. vinifera varieties from Cabernet, Merlot, and Sauvignon groups in a subtropical Cambisol, Southern Brazil. Eight V. vinifera varieties were selected for the field experiment from September 2019 to June 2021. For each studied variety, we established five rectangular plots (60.0 × 14.0 m) using a randomized block design with seven blocks. We found seven main groups considering the dissimilarities of AMF spores: i) Entrophospora claroidea in the root zone of C. Eidos and C. Volos (both varieties from the Cabernet group); ii) Funneliformis mosseae in the root zone of Fleurtai; iii) Racocetra coralloidea in the root zone of Merlot Khantus; iv) Scutellospora calospora in the root zone of M. Khorus; v) Quatunica erytrophus in the root zone of Sauvignon Kretos; vi) Glomus coremioides in the root zone of S. Rytos; and vii) Acaulospora tuberculata in the root zone of Soreli. The results of our study highlighted the importance of considering V. vinifera varieties as potential hosts for specific AMF species by creating an AMF-host pairing specificity to improve root colonisation and plant yield in their own advantage. Thus, field experiments considering V. vinifera varieties into agrosystems for vine production contribute to our understanding of the AMF symbiosis in subtropical soils.